Research on the Mechanisms of Phytohormone Signaling in Regulating Root Development - Yuru Ma; Ying Zhang; Jiahui Xu; Jiahong Qi; Xigang Liu; Lin Guo; Hao Zhang (Plants)
Phytohormones are organic compounds produced in trace amounts within plants that regulate their physiological processes. Their physiological effects are highly complex and diverse. They influence processes ranging from cell division, elongation, and differentiation to plant germination and rooting. Therefore, phytohormones play a crucial regulatory role in plant growth and development. Recently, various studies have highlighted the role of PHs, such as auxin, cytokinin (CK), and abscisic acid (ABA), and newer classes of PHs, such as brassinosteroid (BR) and peptide hormone, in the plant responses toward environmental stresses. These hormones not only have distinct roles at different stages of plant growth but also interact to promote or inhibit each other, thus effectively regulating plant development. Roots are the primary organs for water and mineral absorption in plants. During seed germination, the radicle breaks through the seed coat and grows downward to form the primary root. This occurs because the root needs to quickly penetrate the soil to absorb water and nutrients, providing essential support for the plant’s subsequent growth. Root development is a highly complex and precisely regulated process influenced by various signals. Changes in root architecture can affect the plant’s ability to absorb nutrients and water, which in turn impacts crop yield. Thus, studying the regulation of root development is of great significance. Numerous studies have reported on the role of phytohormones, particularly auxins, in root regulation. This paper reviews recent studies on the regulation of root development by various phytohormones, both individually and in combination, providing a reference for researchers in this field and offering perspectives on future research directions for improving crop yields.